Injury-specific effect of Schwann cell-derived exosome treatment for peripheral nerve injury - Ericka A. Schaeffer; Emily L. Errante; Samuel Nodal; Lisandra Vazquez Diaz; Adham M. Khalafallah; Aisha Khan; W. Dalton Dietrich; Allan D Levi; Stephen Shelby Burks (PLoS ONE, 2026)
Peripheral nerve injury (PNI) is characterized by a loss of cellular and axonal integrity that can lead to limited functional recovery. Because many PNIs are not amenable to repair with traditional techniques, cell therapies have emerged as a treatment option. Exosomes, which can be secreted by Schwann cells (SC), carry cellular signaling molecules that facilitate intercellular communication. Our laboratory and others have success using SC-derived exosomes in preclinical PNI models; however, there is no study that directly compares recovery from different PNIs after exosome treatment. Thus, the currently study investigated if SC-derived exosomes can effectively treat different types of PNI, as measured by axonal regeneration and functional recovery. Adult male Fischer rats were divided into several treatment groups, including nerve transection, reversed autograft, conduit + exosomes, nerve crush, and nerve crush + exosomes. Animals underwent functional assessment through the duration of the experiment and at the conclusion (11 weeks), electrophysiological and histological characteristics were assessed. Results indicate an injury-specific effect of SC-derived exosome treatment. Specifically, exosome treatment improved axon regeneration/myelination, muscle recovery, and gait characteristics for severe, large-gap injuries. These SC-exosome based effects were not observed in crush injuries. Taken together, the results of the current study indicate that there may be differences in recovery based on injury type after PNI and treatment with SC-derived exosomes, potentially due to differences in exosome retention/distribution at the injury site. Future studies should explore how exosomes are distributed following administration across various PNI models, as their therapeutic effects may be more pronounced in upstream regions.